Analysis of the work and of the professional in safety and health at work - Rueda-Mahecha, Yohanna Milena; Martínez Rincón, Julián Andrés; Silva-Giraldo, César Augusto; Martínez García, Carlos Arturo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this article is to carry out an analysis of the work of the occupational health and safety professional and specialist of a group of graduates of this discipline, this process is based on the analysis of four dimensions, the first focused on the demographic part, the second to the socio-labour, the third to the barriers that can arise in the Management of Safety and Health at Work in companies and the fourth focused on technological aspects and innovation in the design, implementation and maintenance of the System Occupational Health and Safety Management.